DUA PUTUSAN YANG BERBEDA TERHADAP KONSISTENSI PENGADILAN DALAM MENYELESAIKAN SENGKETA WANPRESTASI: Analysis of Two Different Decisions On the Courts Consistency in Resolving Default Disputes - Najwa Frisi Meilani; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2026)
Confidentiality agreements in employment relationships often give rise to default disputes, especially when their clauses are considered to limit workers' rights. The formulation of the problem to be discussed is the consistency of the legal considerations of the panel of judges in resolving the dispute of the breach of confidentiality agreement, through the analysis of Decision Number 168/Pdt.G/2024/PN Jkt.Sel and Decision Number 155/Pdt.G/2024/PN Jkt.Sel. The research method used is normative legal research with an analytical descriptive nature, using secondary data in the form of laws and regulations, court decisions, and legal literature. The results of the study show that there are differences in legal interpretation, where one decision integrates civil law, labor law, and constitutional norms, while the other decision only focuses on the legal requirements of the agreement according to the Civil Code. The study's conclusions show that these differences reflect court inconsistencies that have the potential to reduce legal certainty and justice.